2006
DOI: 10.1149/1.2195653
|View full text |Cite
|
Sign up to set email alerts
|

Wafer Strength and Slip Generation Behavior in 300 mm Wafers

Abstract: Dependence of mechanical strength of large diameter wafers as a function of impurity concentration and density of oxide precipitates has been studied in terms of brittle fracture and slip dislocation propagation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In this simple case of interstitial O atoms without interactions between them at higher temperature, the function of the solubility turns out to be the well-known Arrheniustype, and the prefactor is set at 1E23 cm-3 (the density of BC-sites, which is double the Si atom density). These parameters are consistent with those obtained by Mikkelsen: 23 [Oi] = 9E22 exp (−1.52 eV/kT) cm −3 , [3] The formation energy obtained from the ab initio calculations (see Fig. 4) is larger than these values (1.50 eV, 1.52 eV).…”
Section: Case Of Interface Model Without Transition Layerssupporting
confidence: 90%
See 1 more Smart Citation
“…In this simple case of interstitial O atoms without interactions between them at higher temperature, the function of the solubility turns out to be the well-known Arrheniustype, and the prefactor is set at 1E23 cm-3 (the density of BC-sites, which is double the Si atom density). These parameters are consistent with those obtained by Mikkelsen: 23 [Oi] = 9E22 exp (−1.52 eV/kT) cm −3 , [3] The formation energy obtained from the ab initio calculations (see Fig. 4) is larger than these values (1.50 eV, 1.52 eV).…”
Section: Case Of Interface Model Without Transition Layerssupporting
confidence: 90%
“…2 The size of OPs in a wafer for such a high thermal stress process is now smaller than 120 nm. 3 Such an OP without dislocations in its vicinity shows a clear interface with the surrounding Si crystal in a transmission electron microscope (TEM) image. By comparing such an interface with that between the oxide layer and substrate of a thermally oxidized Si wafer, the following two points have been considered as similarities:…”
mentioning
confidence: 99%
“…1,2 However, they are also responsible for decreasing the mechanical strength of Cz-Si wafers if the size and density are not appropriately established. 3 For this reason, strict and highly accurate control of oxygen precipitates over the entire span of a Cz-Si wafer is necessary in order to develop advanced semiconductor devices. In particular, for semiconductor devices that require complicated structural enhancements such as scaling and three-dimensional chip integration, new technology for controlling oxygen precipitates will gain more significance, specifically because endurance against the stress induced in Si wafers during device fabrication is becoming increasingly crucial.…”
mentioning
confidence: 99%
“…Ono et al reported that the generation and the propagation of dislocations during hightemperature annealing in a batch furnace and during rapid thermal processing (RTP) were dramatically suppressed when boron concentration in Si crystals exceeded 8 Â 10 18 cm À3 . 2) Oxygen, which acts as a pinning center for dislocation movements during the annealing process in the batch furnace, has little impact on RTP [2][3][4] since the diffusion time for the oxygen atoms to reach the dislocations is not sufficient. On the other hand, it is well known that the yield stress of a Si wafer strongly depends on the density and the size of oxygen precipitates in Si crystals.…”
mentioning
confidence: 99%
“…On the other hand, it is well known that the yield stress of a Si wafer strongly depends on the density and the size of oxygen precipitates in Si crystals. 2,5) For Si wafers with a diameter of 200 mm, it was reported that the propagation of dislocations due to the thermal stress during batch annealing in a vertical furnace was suppressed by maintaining the density of oxygen precipitates at a value greater than 5 Â 10 9 cm À3 and the size of the precipitates at less than 150 nm. 2) However, RTP using a maximum rampup rate of approximately 100 C/s is popular for device fabrication; therefore, a high thermal stress is induced in the Si wafers.…”
mentioning
confidence: 99%